DEVELOPING CREDIBLE GOVERNMENT LEADERSHIP: INDONESIAN PUBLIC POLICY VIEWS - Uang, Dedy Pribadi; Jalesy, Naaman Marthinus; Situmorang, Alpriyanto; Elvis, Elvis (Fakultas Politik Pemerintahan, 2023)
The Trusted Government Leadership Model: Public Policy Perspectives in Indonesia is the subject of this study's description and analysis. This paper is based on several ideas and earlier research findings that illustrate the dynamics and issues with government leadership specific to regional heads of state. A literature review, including a conceptual analysis of textbooks and earlier research findings pertinent to this study, is the methodology employed. The results demonstrated that competence, goodness, integrity, and policy are the four (four) factors that impact a trustworthy government leadership model. Government leaders must possess the following qualities: (1) competence, which includes knowledge, skills, personality, and managerial abilities; (2) kindness and compassion; (3) integrity, which includes ethics and adherence to the law; and (4) policy, which consists of ten main principles, including the following: (a) public interest; (b) planning; (c) qualified; (d) management; (e) morality; (f) integrated; (g) impact; (h) honour; (i) glorify; and (j) learning.